FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENGGUNAAN APD DIANTARA TENAGA KESEHATAN ZONA MERAH COVID 19 DI RUMAH SAKIT “X” TAHUN 2022 - ALATAS SOFAN SUGARA; BYBA MELDA (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
PPE plays an important role in preventing the transmission of the Covid-19 virus among health workers. The purpose of the study was to determine the factors related to the behavior of using PPE among health workers in the Covid 19 red zone at the "X" Hospital. The research design used a correlation analytic design with a cross sectional approach. The research population was 67 health workers in the Covid 19 red zone at the "X" Hospital and the research sample was 57 respondents with a determination using Simple Random Sampling. The data collection technique used an instrument in the form of a questionnaire sheet. The data analysis method used is the Logistics Regression test. The results showed that the factors related to the behavior of using PPE among inpatient health workers were knowledge (p = 0.002), attitude (p = 0.003), government policy (p = 0.001) and the availability of PPE (p = 0.003). Further researchers need to know other factors that influence the behavior of using PPE, including the habit of using smartphones at work and personal hygiene.